2021
DOI: 10.14245/ns.2040640.320
|View full text |Cite
|
Sign up to set email alerts
|

Transumbilical Retroperitoneal Lumbar Interbody Fusion: A Technical Note and Preliminary Case Series

Abstract: Objective: Anterior lumbar interbody fusion (ALIF) has advantages over posterior lumbar interbody fusion or transforaminal lumbar interbody fusion techniques in that it minimizes damage to the anatomical structure of the posterior spinal segment and enables indirect decompression of the foramen by insertion of a tall cage. However, the predominant abdominal scar tissue reduces patients' satisfaction after ALIF. Herein, we describe the technique of transumbilical lumbar interbody fusion (TULIF) and its prelimin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…1,2 Traditionally, many kinds of lumbar interbody fusions have been conducted, such as posterior lumbar interbody fusion (PLIF), transforaminal lumbar interbody fusion (TLIF), anterior lumbar interbody fusion (ALIF), and direct lumbar interbody fusion using different approaches and fusion materials. [2][3][4][5][6][7][8][9] In recent years, TLIF can be performed via a minimally invasive surgical (MIS) approach, which can reduce the denervation of multifidus muscle as well as reduce the incidence of intramuscular degeneration and necrosis. 4,[6][7][8] However, patients undergoing MIS-TLIF often suffer from chronic back pain after surgery, owing to the resection of paravertebral muscles and facet joints.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 Traditionally, many kinds of lumbar interbody fusions have been conducted, such as posterior lumbar interbody fusion (PLIF), transforaminal lumbar interbody fusion (TLIF), anterior lumbar interbody fusion (ALIF), and direct lumbar interbody fusion using different approaches and fusion materials. [2][3][4][5][6][7][8][9] In recent years, TLIF can be performed via a minimally invasive surgical (MIS) approach, which can reduce the denervation of multifidus muscle as well as reduce the incidence of intramuscular degeneration and necrosis. 4,[6][7][8] However, patients undergoing MIS-TLIF often suffer from chronic back pain after surgery, owing to the resection of paravertebral muscles and facet joints.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, Bae et al [ 9 ] reported that using the method using transumbilical retroperitoneal lumbar interbody fusion, although technically difficult, both the treatment of degenerative spinal diseases and satisfactory cosmetic results could be achieved.…”
mentioning
confidence: 99%